A calorimetric test of adsorbent-coated fins. (March 2018) - Ahamat, Mohamad A.; Tierney, Michael J.
Highlights: Calorimetric assessment of adsorption rates has been attempted on finned adsorbents. The method detects differences in adsorption rate between different substrates: flat plates, aluminium and steel fins. The results have implications for the performance enhancement of adsorption heat pumps. Abstract: Adsorption heat pumps often use coated prismatic fins. This paper concerns a calorimetric test of different types of coated fins. Samples of substrate-plus-adsorbent were kept at constant temperature by a thermoelectric module (TEM) but subjected to a step change in vapour pressure (large pressure jump, LPJ). The TEM had been calibrated to yield the quantity of heat transferred to the TEM and hence the heat rejected by the sample. (The TEM was mounted on the outer surface of the test vessel in order to eliminate the impact on the sample of degassing and corrosion of the TEM by the water vapour used.) The plot of heat rejected from the fin base versus time fitted an exponential function. Thereupon a ratio of characteristic times indicated performance of coated fins (the numerator referred to the fin and the denominator to an isothermal flat plate). The ratio was 1.07 for 3-mm-diameter beads adhered to aluminium fins and this demonstrated an example where the axial temperature gradients in the fin were unimportant. In a steel fin a larger ratio of characteristic times (∼2) demonstrated the impact of strong axial temperature gradients. Crudely inferred values of specific cooling power (SCP) were broadly comparable to values reported for other combinations of substrate, adsorbent and adsorbate.